Grupo Ginástico UNESP: contribuições da Ginástica para Todos na formação de seus participantes - Afonso, Paulo Roveri de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Gymnastics for all or General Gymnastics is a gymnastic body practice without competitive purposes, demonstrative character that combines the basics of gymnastics with different forms of body language. It is a pleasurable physical activity and inclusive, within the gymnastic possibilities offers great opportunities for participation of people, creativity, cooperation and human values experiences (AYOUB, 2003). Within this proposal is, in 2011, the Gymnastic Group UNESP, under the guidance and coordination of teachers Laurita Marconi Schiavon e Silvia Deustch as a project of university extension of the Department of Physical Education, Biosciences Institute of the São Paulo State University / Campus Rio Claro - SP. His working method and choreographic composition based on the proposal of the Gymnastic Group Unicamp, reference in this body practice in Brazil, and their course is in two parts: one for the exploration of all the resources that the teaching materials can provide and the other focused on social interaction of its participants. Therefore the research developed in this study aimed to verify contributions of the participation of members in Gymnastic Group Unesp vocational training thereof, and to verify the relationship and the approach of the members with Gym. The methodological approach adopted for this qualitative research is descriptive, and quantitative and qualitative data collected through questionnaires. The participants were 32 students from different courses at the University, and members of Gymnastic Unesp Group from 2011 to 2013, with the inclusion criteria: 1. minimum of one year of participation in Gymnastic Group Unesp; 2. Minimum of two performances of choreography in events with that group. Quantitative data are processed using descriptive statistics and qualitative analyzed by content analysis technique proposed by Laville and Dionne (1999). According to the results obtained over 41% of the participants had no...

A Ginástica para todos ou Ginástica Geral é uma prática corporal gímnica, sem fins competitivos, de caráter demonstrativo, que combina os fundamentos da ginástica com diferentes formas de expressão corporal. É uma atividade física prazerosa e inclusiva e dentro das possibilidades gímnicas oferece grandes oportunidades de participação das pessoas, criatividade, cooperação e de vivências de valores humanos (AYOUB, 2003). Dentro desta proposta surge, em 2011, o Grupo Ginástico Unesp, sob a orientação e coordenação das professoras Laurita Marconi Schiavon e Silvia Deustch, como um projeto de extensão universitária do Departamento de Educação Física, Instituto de Biociências da Universidade Estadual Paulista/Campus Rio Claro - SP. Seu método de trabalho e de composição coreográfica baseia-se na proposta do Grupo Ginástico Unicamp, referência nesta prática corporal no Brasil, que se constitui em duas partes: uma delas destinada à exploração de todos os recursos que o material pedagógico pode proporcionar e a outra voltada para a interação social de seus participantes. Sendo assim a pesquisa desenvolvida neste estudo teve como objetivo principal verificar contribuições da participação dos integrantes no Grupo Ginástico Unesp na formação profissional dos mesmos, além de verificar a relação e a aproximação dos integrantes com a Ginástica. A abordagem metodológica adotada para esta pesquisa qualitativa foi de caráter descritivo, com dados quantitativos e qualitativos, coletados por meio de questionários. Os participantes da pesquisa foram 32 universitários, de diferentes cursos da Universidade, e membros do Grupo Ginástico Unesp de 2011 a 2013, tendo como critérios de inclusão: 1. mínimo de um ano de participação no Grupo Ginástico Unesp; 2. Mínimo de duas apresentações de coreografias em eventos com o referido Grupo. Os dados quantitativos foram tratados por estatística descritiva e...
Keywords: Ginástica; Extensão universitaria; Formação profissional; Ginástica - História - 2011-2013 - Rio Claro (SP)